Organizational Commitment and Job Satisfaction Towards Organizational Citizenship Behavior (OCB) Employees of PT Anugerah Sekuritas Indonesia - Anggi Setyawati; Marisi Pakpahan; Prasastiara Eka Marsella (Indonesia Banking School, 2024)
The objectives of this research are: 1) To determine and analyze the influence of Organizational Commitment on Organizational Citizenship Behavior (OCB) of PT Anugerah Sekuritas Indonesia employees. 2) To determine and analyze the influence of Job Satisfaction on Organizational Citizenship Behavior (OCB) of PT Anugerah Sekuritas Indonesia employees. 3) To determine and analyze the influence of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior (OCB) of PT Anugerah Sekuritas Indonesia employees. The research method used is a quantitative method. The results of this research show that Organizational Commitment has a significant effect on Organizational Citizenship Behavior, the level of correlation relationship is very strong and is marked by a value of 82% indicating the positive contribution of Organizational Commitment to Organizational Citizenship Behavior and Job Satisfaction has a significant effect on Organizational Citizenship Behavior, the level of correlation relationship is very strong and marked with a value of 80.8% indicating a positive contribution from Job Satisfaction to Organizational Citizenship Behavior and Organizational Commitment and Job Satisfaction simultaneously influence Organizational Citizenship Behavior and marked with a value of 85.7% indicating a positive contribution from Organizational Commitment and Job Satisfaction simultaneous influence on Organizational Citizenship Behavior. This value increases when both variables are analyzed simultaneously (together).